Design and parametric evaluation of UWB antenna for array arrangement - Faraz Ahmed Shaikh; Sheroz Khan; A H. M. Zahirul Alam; Dominique Baillargeat; Mohamed Hadi Habaebi; Mashkuri Bin Yaacob; Jawad Shah; Zeeshan Shahid (Institute of Advanced Engineering and Science, 2019)
This paper has introduced the concept of UWB antenna in array arrangements. The four elements of Balance Antipodal Vivaldi Antenna (BAVA) has been used for planar and H-plane array configuration in this research. Each single element of BAVA Antenna is printed on the glass-reinforced epoxy laminate material (FR4) along an overall thickness of 1.57mm and εr=4.3 respectively. The optimized measurement of each particular element is 60.75mm x 66mm approximatel. Further the parametric evaluation of four BAVA elements in different planes has been observed in this paper. The placement of array elements has almost coverd entire UWB frequency range and appropriate reflection coefficient which is better than -10dB has been established in both combinations. According to simulation results, the array elements in planar arrangement presenting a suitable reflection and works well at 3.2GHz frequency while the arrangement in H-plane the array elements works well at 7GHz of frequency. In planar arrangement, the operating frequency of antenna elements is shifting as results of the distance among inter elements which increase in wavelength. In H-plane arrangement an antenna elements generate additional gain up to 10.2 dB with good radiation patterns as compared to the planar plane. The CSTMWS simulation software has been used for antenna structural design and parametric verification.